Manipulation of p53 Protein in Bladder Cancer Treatment - Mansor, Siti Farizan (IIUM Medical Journal Malaysia, 2021)
Chemotherapy and radiotherapy are gold standard treatment for bladder cancer (BC) for over 50 years. The efficacy on early stage BC patients is virtuous. However, patients with aggressive cancer growth benefited less from the therapy. Aberrant p53 was found in more than 50% of high-grade BC patients. Therefore, targeting p53 in a subset of high-grade BC patients expressing aberrant p53 is a promising strategy. In this paper, p53 role in BC carcinogenesis is discussed. Followed by p53-targeting strategies in current BC treatment. Besides, p53-targeting strategies that have been implemented in other types of cancer and their potential to be adapted in BC will be deliberated. Although targeting p53 is promising, none of the strategies studied were successfully implemented in healthcare settings. Restoration of p53 as the guardian of the genome is an exciting area for translational research. It has potential to replace the genotoxic chemotherapy and radiotherapy, thus, eliminating the notorious painful sideeffects on a subset of high-grade BC patients. Searches were performed on PubMed and Google Scholar web using the keywords “bladder cancer” or “urothelial cancer” or “urothelial cell carcinoma” and “p53”. Only full papers of research articles and review papers were included for analysis. Papers were categorized as either p53 function, current treatment using p53 and future potential treatment using p53 for details analysis.